Effect of Temperature Variation on Bond Characteristics between CFRP and Steel Plate. (4th December 2016) - Li, Shan; Zhu, Tao; Lu, Yiyan; Li, Xiaojin
Abstract : In recent years, application of carbon fiber reinforced polymer (CFRP) composite materials in the strengthening of existing reinforced concrete structures has gained widespread attention, but the retrofitting of metallic buildings and bridges with CFRP is still in its early stages. In real life, these structures are possibly subjected to dry and hot climate. Therefore, it is necessary to understand the bond behavior between CFRP and steel at different temperatures. To examine the bond between CFRP and steel under hot climate, a total of twenty-one double strap joints divided into 7 groups were tested to failure at constant temperatures from 27°C to 120°C in this paper. The results showed that the joint failure mode changed from debonding along between steel and adhesive interface failure to debonding along between CFRP and adhesive interface failure as the temperature increased beyond the glass transition temperature (T g ) of the adhesive. The load carrying capacity decreased significantly at temperatures approaching or exceeding T g . The interfacial fracture energy showed a similar degradation trend. Analytical models of the ultimate bearing capacity, interfacial fracture energy, and bond-slip relationship of CFRP-steel interface at elevated temperatures were presented.